Clinical implementation of an exit detector‐based dose reconstruction tool for helical tomotherapy delivery quality assurance. Issue 10 (22nd August 2017) - Deshpande, Shrikant; Xing, Aitang; Metcalfe, Peter; Holloway, Lois; Vial, Philip; Geurts, Mark
Abstract : Purpose: The aim of this study was to validate the accuracy of an exit detector‐based dose reconstruction tool for helical tomotherapy (HT) delivery quality assurance (DQA). Methods and material: Exit detector‐based DQA tool was developed for patient‐specific HT treatment verification. The tool performs a dose reconstruction on the planning image using the sinogram measured by the HT exit detector with no objects in the beam (i.e., static couch), and compares the reconstructed dose to the planned dose. Vendor supplied (three "TomoPhant") plans with a cylindrical solid water ("cheese") phantom were used for validation. Each "TomoPhant" plan was modified with intentional multileaf collimator leaf open time (MLC LOT) errors to assess the sensitivity and robustness of this tool. Four scenarios were tested; leaf 32 was "stuck open, " leaf 42 was "stuck open, " random leaf LOT was closed first by mean values of 2% and then 4%. A static couch DQA procedure was then run five times (once with the unmodified sinogram and four times with modified sinograms) for each of the three "TomoPhant" treatment plans. First, the original optimized delivery plan was compared with the original machine agnostic delivery plan, then the original optimized plans with a known modification applied (intentional MLC LOT error) were compared to the corresponding error plan exit detector measurements. An absolute dose comparison between calculated and ion chamber (A1SL, Standard Imaging, Inc., WI, USA) measured dose was performed for the unmodified "TomoPhant" plans. A 3D gamma evaluation (2%/2 mm global) was performed by comparing the planned dose ("original planned dose" for unmodified plans and "adjusted planned dose" for each intentional error) to exit detector‐reconstructed dose for all three "Tomophant" plans. Finally, DQA for 119 clinical (treatment length <25 cm) and three cranio‐spinal irradiation (CSI) plans were measured with both the ArcCHECK phantom (Sun Nuclear Corp., Melbourne, FL, USA) and the exit detector DQA tool to assess the time required for DQA and similarity between two methods. Results: The measured ion chamber dose agreed to within 1.5% of the reconstructed dose computed by the exit detector DQA tool on a cheese phantom for all unmodified "Tomophant" plans. Excellent agreement in gamma pass rate (>95%) was observed between the planned and reconstructed dose for all "Tomophant" plans considered using the tool. The gamma pass rate from 119 clinical plan DQA measurements was 94.9% ± 1.5% and 91.9% ± 4.37% for the exit detector DQA tool and ArcCHECK phantom measurements ( P  = 0.81), respectively. For the clinical plans (treatment length <25 cm), the average time required to perform DQA was 24.7 ± 3.5 and 39.5 ± 4.5 min using the exit detector QA tool and ArcCHECK phantom, respectively, whereas the average time required for the 3 CSI treatments was 35 ± 3.5 and 90 ± 5.2 min, respectively. Conclusion: The exit detector tool has been demonstrated to be faster for performing the DQA with equivalent sensitivity for detecting MLC LOT errors relative to a conventional phantom‐based QA method. In addition, comprehensive MLC performance evaluation and features of reconstructed dose provide additional insight into understanding DQA failures and the clinical relevance of DQA results.